Konstruoidun toiminnan kehystämisen strategiat suomalaisen viittomakielen tarina- ja keskusteluaineistossa - Varttinen, Kirsi (2024)
This Master’s thesis examines the strategies of framing constructed action (CA) — i.e. identifying the referent prior to the constructed action — in Finnish Sign Language (FinSL) narratives and conversational context. Since the strategies of framing constructed action have not been previously studied in Finnish Sign Language, the classification of referencing is based on the work of Cormier, Smith & Zwets (2013): contiguous reference (NP CA), non-contiguous reference (NP…CA) and omission of nominal phrase (ZeroNP CA) where no framing occurs. In addition to the general analysis of the strategies, the variation between signers has also been observed. The research questions are: 1. What kind of strategies are used in framing constructed action in Finnish Sign Language? 2. How are the strategies distributed in narratives and conversational context and between the individuals? The research material is from the ShowTell-project, and it is a sample of the narrative and conversational context of the corpus material of Finnish Sign Language. Since the text genre and the age of the signer are known to affect the use of constructed action, two text types (narratives and conversations) have been selected for comparison. The group of signers has also been constrained by age (aged 30-50). The strategies of framing were annotated using the application ELAN and they were analyzed quantitatively. Qualitative method was used in the analysis of the data and the comparison of the text types. According to the results, all the three strategies of framing occur in Finnish Sign Language — both in narratives and in conversational context. In the narratives, strategies of framing are used somewhat similarly between the signers, while in the conversational context the variation appears to be higher. The results of this study raise the question: what the framing of constructed action in sign language ultimately means? In the future, the research of strategies of framing should also be extended to cover the possibilities of referentiality during constructed action, and also take the individuals and the situation of interaction into account. Signed language seems to make it possible that framing constructed action in its traditional sense is not necessarily always needed.